Type 2 diabetes mellitus in glucose-6-phosphate dehydrogenase deficient individuals in a Ghanaian population - Quartey, Perez; Owusu, Bright Afriyie; Taylor, Daniel; Adomaka, Eliza-Bertha (International Journal of Research in Medical Sciences, 2020)
Background: Studies in different populations have shown an association between diabetes mellitus and G6PD deficiency. This association has not been investigated in the Ghanaian population. We conducted a cross-sectional study to investigate the relationship between G6PD deficiency and type 2 diabetes mellitus in a Ghanaian population. Methods: The cross-sectional study involved 125 registered type 2 diabetes mellitus clients and 125 non-diabetic individuals. Chi-square analysis was used to assess the association between G6PD status and type 2 diabetes mellitus with statistical significance pegged at p-value<0.05. Results: The prevalence of G6PD deficiency in the study population was 24.0% and 13.6% for the diabetics and non-diabetics respectively. In terms of gender, 29.5% of the diabetic males were G6PD deficient whiles G6PD deficiency was observed in 11.1% of the non-diabetic males. Additionally, 21.0% of the diabetic females were also G6PD deficient with 15.3% of the non-diabetic females being G6PD deficient. The results showed that the overall G6PD deficiency was significantly associated with type 2 diabetes mellitus as compared to the non-diabetics. In terms of gender differences, G6PD deficiency was significantly associated with type 2 diabetes in males but, there was no significant association in females. Conclusions: The study reports the first findings of the relationship between G6PD deficiencies among type 2 diabetes patients in Ghana. The study revealed that G6PD deficiency is more prevalent among type 2 diabetics than non-diabetics. Type 2 diabetes mellitus is independently associated with G6PD deficiency in males but not females.